Integrating Culture with Counselling: Children who have Experienced Trauma. - Vogel, Dalena (International Journal of the Humanities, 2011)
In South Africa, many children grow up in dysfunctional family environments. Many experience this as a crisis and develop problem behaviours such as depression, anger, learning problems and even physical conditions from emotional reactions to their crisis. Their coping skills appear to be ineffective and they have not acquired the necessary life skills from parents or caregivers to handle a life crisis successfully. The role of a child counsellor is to help the client to understand his or her past and current experiences and integrate the two meaningfully into a new life story with hope and motivation for a positive future. The article is based on literature research, discussions with teachers, parents and psychologists, hours of trauma counselling sessions, and workshops on child trauma counselling. It includes one case study and a proposed model for trauma counselling in South Africa.